Presentation and Evaluation of the IPSL‐CM6A‐LR Climate Model. (20th July 2020) - Boucher, Olivier; Servonnat, Jérôme; Albright, Anna Lea; Aumont, Olivier; Balkanski, Yves; Bastrikov, Vladislav; Bekki, Slimane; Bonnet, Rémy; Bony, Sandrine; Bopp, Laurent; Braconnot, Pascale; Brockmann, Patrick; et al.
Abstract: This study presents the global climate model IPSL‐CM6A‐LR developed at Institut Pierre‐Simon Laplace (IPSL) to study natural climate variability and climate response to natural and anthropogenic forcings as part of the sixth phase of the Coupled Model Intercomparison Project (CMIP6). This article describes the different model components, their coupling, and the simulated climate in comparison to previous model versions. We focus here on the representation of the physical climate along with the main characteristics of the global carbon cycle. The model's climatology, as assessed from a range of metrics (related in particular to radiation, temperature, precipitation, and wind), is strongly improved in comparison to previous model versions. Although they are reduced, a number of known biases and shortcomings (e.g., double Intertropical Convergence Zone [ITCZ], frequency of midlatitude wintertime blockings, and El Niño–Southern Oscillation [ENSO] dynamics) persist. The equilibrium climate sensitivity and transient climate response have both increased from the previous climate model IPSL‐CM5A‐LR used in CMIP5. A large ensemble of more than 30 members for the historical period (1850–2018) and a smaller ensemble for a range of emissions scenarios (until 2100 and 2300) are also presented and discussed. Plain Language Summary: Climate models are unique tools to investigate the characteristics and behavior of the climate system. While climate models and their components are developed gradually over the years, the sixth phase of the Coupled Model Intercomparison Project (CMIP6) has been the opportunity for the Institut Pierre‐Simon Laplace to develop, test, and evaluate a new configuration of its climate model called IPSL‐CM6A‐LR. The characteristics and emerging properties of this new model are presented in this study. The model climatology, as assessed from a range of metrics, is strongly improved, although a number of biases common to many models do persist. The equilibrium climate sensitivity and transient climate response have both increased from the previous climate model IPSL‐CM5A‐LR used in CMIP5. Key Points: The IPSL‐CM6A‐LR model climatology is much improved over the previous version, although some systematic biases and shortcomings persist A long preindustrial control and a large number of historical and scenario simulations have been performed as part of CMIP6 The effective climate sensitivity of the IPSL model increases from 4.1 to 4.8 K between IPSL‐CM5A‐LR and IPSL‐CM6A‐LR